Пацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезнуюПацанам привет остальным соболезную
Объяснение:
ху(х+у)(х-у-8)
Объяснение:
(ху+у²)(х²-4х)-(х²+ху)(у²+4у)=
=х³у+х²у²-4х²у-4ху²-х²у²-ху³-4х²у-4ху²=
=(х²у-х²у)+(-4ху²-4ху²)+(-4х²у-4х²у)+х³у-ху³=
=-8ху²-8х²у+х³у-ху³=
=(-8ху²-8х²у)+(х³у-ху³)=
=-8ху(у+х) +ху(х²-у²)=
=-8ху(х+у)+ху(х-у)(х+у)=
=ху(х+у)(х-у-8)